PENGARUH PROFITABILITAS, STRUKTUR AKTIVA DAN UKURAN PERUSAHAAN TERHADAP STRUKTUR MODAL PERUSAHAAN MANUFAKTUR SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Dian Pisesah; Anik Malikah; Junaidi Junaidi (Universitas Islam Malang, 2021)
This study aims to determine the effect of profitability, asset structure and company size on the capital structure of the food and beverage sector manufacturing companies listed on the Indonesia stock exchange in the 2016-2018 period. The number of samples of this study were 11 companies, the sample of this study was determined by purposive sampling method. Data collection uses the documentation method which is the method used to obtain data and information in the form of books, archives, documents, writing numbers and images in the form of reports and about theories relating to the problem being studied. Based on the results of this study concluded that Profitability (Return on assets / ROA) has a significant negative effect on the variable capital structure (Debt to Equity Ratio). Asset Structure (Fixed Assets to Total Assets / FATA) has a significant positive effect on the capital structure variable (Debt to Equity Ratio) and Company Size (SIZE) has a significant positive effect on the capital structure variable (Debt to Equity Ratio).Keywords: Profitability (ROA), Asset Structure (FATA), Firm Size (SIZE) and Capital Structure (DER).